Primary pulmonary extranodal NK/T-cell lymphoma diagnosed by thoracoscopic lung biopsy: A case report - Michihiko Tanaka; Yasushi Horimasu; Kazuma Kawamoto; Taro Edahiro; Kakuhiro Yamaguchi; Shinjiro Sakamoto; Takeshi Masuda; Taku Nakashima; Hiroshi Iwamoto; Kazunori Fujitaka; Hironobu Hamada; Tatsuo Ichinohe; et al. (Respiratory Medicine Case Reports)
A 63-year-old Japanese female presented with fever. Computed tomography showed multiple nodules in both lungs. Corticosteroids and antibiotics were administered to treat suspected organizing and bacterial pneumonia, resulting in no improvement and respiratory failure worsened. Surgical lung biopsy revealed infiltration of CD3, CD56, Granzyme B, and EBV-encoded RNA-ISH-positive atypical lymphocytes. She was diagnosed with primary pulmonary extranodal NK/T-cell lymphoma (ENKL) and died two months after diagnosis with only a temporary effectiveness of chemotherapy. We should consider the possibility of ENKL and perform prompt and appropriate biopsy for early diagnosis in cases where empiric therapy is ineffective for suspected pneumonia.